The Role of Gender Identity and Sex in Self–objectification (Annual of the Faculty of Philosophy in Skopje, 2018)
The overall aim of this study was to explore the relationships among self-ob- jectification and gender identity in young women and men. Two self-objectification aspects (body surveillance and body shame), exercise activity and time spent in “beautifying” were investigated in relation to sex, gender identity. A sample of340 ethnic Macedonians (50% male) at average age of M=25.21 years (SD=5.60) participated in the study by providing background information (including self-assessed time spent in physical activity and beautifying) and fulfilling two subscales of the Objectified Body Consciousness Scale (McKinley & Hyde, 1996) and Femininity/Masculinity trait index scale (Barak & Stern, 1986). The three hypotheses were tested by using two-way AN OVA and correlation coefficients and all of them were partially confirmed. The author concludes that women tend to self-objectify themselves more than men and that this tendency is in interaction with the extent to which one identifies her/himself with the gender role. In addition, results suggest that self-objectification is connected to different health-related behaviour of women and men.
Keywords: SELF-OBJECTIFICATION; GENDER IDENTITY; SEX